The new lesbian aesthetic? Exploring gender style among femme, butch and androgynous sexual minority women - Gunn, Audrey; Hoskin, Rhea Ashley; Blair, Karen L. (Women's Studies International Forum, 2021)
The current study explored sexual minority women’s gender aesthetic and style by using van Anders’ (2015) sexual configurations theory (SCT), which allows for nuance in the measurement of gender/sex research. Previous research on sexual minority women has suggested a markedly masculine “Lesbian Aesthetic” (Huxley et al., 2014) and has connected aesthetic expression to internalized homophobia and levels of outness such that sexual minority women categorized as more feminine report higher rates of internalized homophobia and identity concealment. However, the bulk of past research used dichotomous measures of assessing gender and predated an ostensible shift in LGBTQ+ identities. To update this body of research, the current study explored gender aesthetics by asking sexual minority women to map their gender expression using SCT diagrams and complete measures of outness and internalized homophobia. We found no significant group differences in internalized homophobia or outness for femme, butch, and androgynous participants. Content analyses of gender diagrams suggest that the gender aesthetics of sexual minority women are neither monolithic nor masculine but may be beginning to lean towards the feminine and most certainly encompass a complex and diverse range of expressions
Keywords: amériques; approches et analyses; canada; discipline; homophobie; hétérosexisme; identités LGBTQIA2+; lesbophobie; psychologie; queer; ressource en ligne; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions